2017
DOI: 10.1523/eneuro.0314-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Natural Echolocation Sequences in the Inferior Colliculus of Seba’s Fruit Eating Bat,Carollia perspicillata

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 148 publications
(185 reference statements)
4
32
2
Order By: Relevance
“…The results show that cortical neurons responded primarily to echoes from the closest object. The suppression of responses to echoes at longer delays observed in cortical neurons was absent in the IC, and Beetz et al (2017) suggested that parallel processing of multiple echoes at the level of the midbrain IC might drive cortical representation of the closer objects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results show that cortical neurons responded primarily to echoes from the closest object. The suppression of responses to echoes at longer delays observed in cortical neurons was absent in the IC, and Beetz et al (2017) suggested that parallel processing of multiple echoes at the level of the midbrain IC might drive cortical representation of the closer objects.…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiological studies in several bat species have measured single unit responses to broadcasts of natural echolocation sequences, which contained echoes from one or more objects (Bartenstein et al, 2014;Beetz et al, 2016Beetz et al, , 2017Greiter and Firzlaff, 2017;Macias et al, 2018;Sanderson and Simmons, 2000). For example, researchers presented the anesthetized FM bat Phyllostomus discolor with acoustic pulse-echo stimuli that simulated the bat's decreasing distance to one (Bartenstein et al, 2014) or two (Greiter and Firzlaff, 2017) objects, and characterized single-unit responses in the auditory cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that bats were not able to move during the recordings, their heads were fixed by holding a metal rod attached to the scalp. The surgical procedure for metal rod fixation has been described elsewhere 41,92,95 . Briefly, in fully anesthetized bats (Ketamine (10 mg *kg − 1 Ketavet, Pfizer) and Xylazine (38 mg *kg − 1 Rompun, Bayer)), the skin and muscles covering the scalp were removed.…”
Section: Setup For Dpoae Measurementsmentioning
confidence: 99%